Implementation of “Kurikulum Merdeka” to Develop Children’s Fine Motor Skills in Raudathul Athfals (RA) Jambi City - Hs, Elida; Pujiarto, Pujiarto (Kirana Publisher (KNPub), 2024)
Providing a good environment for children should be a priority for parents and their educators, because the environment can be a means of learning for children. This research aims to provide an overview of how structuring a play environment can provide a stimulus to help the fine motor skills of young children grow. Qualitative research using observation, interviews, documentation and field notes as data collection methods. It is set in three schools, namely RA Halimatusa'diah, RA Ahsan, and RA Iqra' Sabila located in Jambi province which was assisted by teaching staff there to obtain the data sought. This research found that the implementation of the play environment arrangement was considered successful in stimulating the fine motor development of young children in three Raudathul Athfals (RA).